Perfil de resistência a antimicrobianos de estirpes de Escherichia coli, Staphylococcus aureus e Salmonella sp. isoladas de amostras de produtos de origem animal provenientes de feiras e supermercados de São Luís - Souza, Jaqueline Freitas (2022)
The accelerated development of multidrug-resistant pathogens is very worrying, as existing factors such as the lack of therapeutic options for the treatment of infections caused by resistant bacteria and the high mortality rates have been increasing. In order to evaluate the antimicrobial resistance profile of strains of Escherichia coli, Staphylococcus aureus and Salmonella sp. isolated from samples of animal products from fairs and supermarkets in São Luís - MA. A total of 213 samples were analyzed, 44 samples of dried meat, 41 of chicken, 43 of ground meat, 44 of fish and 41 of cheese. As for the presence of E. coli, S. aureus and Salmonella sp. through conventional methodology and classified according to the microbiological standard of the National Health Surveillance Agency. Bacterial isolates were tested for susceptibility to 6 classes of antimicrobials, following the Disc Diffusion method. S. aureus was identified in 41 samples of dried meat, 20 of chicken, 30 of ground meat, 15 of fish and 35 of cheese. The presence of E. coli was confirmed in 10 samples of dried meat, 13 of chicken, 11 of ground meat, 12 of fish and 10 of cheese. For Salmonella sp., two samples of chicken and two of fish were contaminated. As for the resistance profile, 16 showed resistance to one antimicrobial and 97 to more than one antimicrobial to S. aureus. being considered multidrug resistant. For E. coli one showed resistance to one antimicrobial and 39 to more than one antibiotic. And Salmonella sp., 100% were considered sensitive to five antimicrobials. Based on the results found, there is a need for permanent surveillance in the use of antibiotics in veterinary medicine